Clinical efficacy of low‐dose Perampanel correlates with neurophysiological changes in familial adult myoclonus epilepsy 2 - Antonietta Coppola; Claudia Cuccurullo; Gianmaria Senerchia; Marica Rubino; Liana Veneziano; Francesco Brancati; Luigi Baratto; Valentina Virginia Iuzzolino; Leonilda Bilo; Pasquale Striano; Raffaele Dubbioso (Epilepsia Open)
Abstract Familial adult myoclonus epilepsy (FAME) management relies on antiseizure medications (ASMs), which inadequately address myoclonus and cortical tremor. This study evaluates Perampanel (PER), an AMPA‐receptor antagonist, for treating FAME symptoms. Fifteen FAME2 patients participated in an observational prospective study. They received up to 6 mg daily of PER and underwent Unified‐Myoclonus‐Rating‐Scale (UMRS) before and after treatment. Neurophysiological evaluations, including somatosensory evoked potentials (SEPs) and transcranial magnetic stimulation (TMS), assessed PER's impact on cortical glutamatergic excitatory and GABAergic inhibitory circuits. PER treatment significantly reduced UMRS total scores (p = 0.001) and action‐myoclonus subscores (p = 0.002), irrespective of disease duration, age at onset, or testing time (p >0.05). Patients with more severe baseline myoclonus demonstrated significant improvements. Neurophysiological assessments revealed a PER‐induced decrease in sensorimotor hyperexcitability, characterized by diminished N33 amplitudes, attenuated glutamatergic facilitation, and enhanced GABAergic inhibition in the motor cortex. In conclusion, low‐dose PER is well tolerated and effective in alleviating myoclonus in FAME2 patients, supported by its modulatory effects on glutamatergic and GABAergic neuronal circuits. Plain Language Summary: This study investigated the effects of low‐dose perampanel in individuals with Familial Adult Myoclonus Epilepsy2 (FAME2), a hereditary condition characterized by epilepsy and tremors. Perampanel, an antiepileptic drug, blocks AMPA receptors in the brain, reducing excessive neural activity that causes seizures and abnormal movements. The results showed significant symptom improvement, which correlated with changes in brain activity as measured by neurophysiological tests. This study suggests that perampanel helps regulate abnormal brain signals and may help managing FAME2 symptoms.